La prévention des inondations dans les opérations d'aménagement des interfaces ville-port, un levier de gentrification indirecte ? Le cas du Havre (France) - Florence Orillard; Mathilde Gralepois; Laura Verdelli (Carnets de Géographes, 2018)
Among the studies on natural risks, spatial transformations and local governance, the paper aims to analyse how flood prevention rules are implemented as political instruments to pursue gentrification, as if flood rules can justify high standing level renewal of old poor areas. Flood prevention rules and measures in some industrial-harbour areas are used to legitimate indirect gentrification. Arguing for collective security and necessity of growth, at the end, the city is strategically developed on flood prone areas. For instance, in Le Havre (France), even if the gentrification is clearly visible, there are no complaints. How can it be explained? Cities are more and more submitted to competitiveness, and even more if they belong to the industrial harbour cities that need to be visible at a worldwide scale. The city of Le Havre is a textbook to illustrate the challenges of declining industrial cities. To stimulate the competitiveness, Le Havre is capitalizing its heritage strengths through new urban projects. These rapidly developing urban areas in industrial-harbour zones bring wealthy new residents and businesses and promote a new face and image of the city, while threatening long-standing poorer residents. These urban projects invoke the heritage of the past maritime tradition, in order to reinvent an attractive landscape. Usually, this indirect gentrification comes together with protest movements, but the integration of risk prevention measures in the resilient urban project seems enough to justify the socio-economic upgrading of the area.